1982
DOI: 10.1161/01.str.13.4.505
|View full text |Cite
|
Sign up to set email alerts
|

An animal model of cerebral infarction. Homologous blood clot emboli in rats.

Abstract: SUMMARY An experimental model of cerebral infarction is created in rats by intracarotid injection of their homologous blood clots. This is the first small animal model in which embolization was achieved by homologous blood clots. The infarcts were produced predominantly in the territory of the middle cerebral artery. The low mortality rate and excellent reproduction rate make possible the correlative study of morphological, biochemical, and metabolic parameters at selected points in time to reconstruct the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
2
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 8 publications
1
79
2
2
Order By: Relevance
“…Clinical manifestations were improved in most animals by 48 h after embolization, but the infarction area was observed until 120 h later. A previous report also showed that clinical signs were much improved by the 5th day after embolization (9). The reason for this discrepancy is not clear from the present study.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Clinical manifestations were improved in most animals by 48 h after embolization, but the infarction area was observed until 120 h later. A previous report also showed that clinical signs were much improved by the 5th day after embolization (9). The reason for this discrepancy is not clear from the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…This model is distinct from other blood clot embolic models in terms of the induction of ischemia. The blood clot embolic models previously reported are induced by injection of clots through the common carotid artery (9) or through a catheter attached to the external carotid artery (10). Although these models are closer than suture models to what actually happens in patients with stroke, they exhibit problems of non-uniformity in the infarction area and technical difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a high probability that the MCA is the recipient of emboli, the location of infarcts in these models is not reproducible. 11 This difficulty was overcome by a local delivery of an intact fibrin-rich embolus into the segment of the ICA near the origin of the MCA. 12 Similar strategies were developed in mice by using injection of microemboli.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Other workers have used a second type of model involving injection of autologous or heterologous preformed fibrin, blood clots, 11,12,13 including microemboli, 14 or in situ clot formation by using rose Bengal. 15,16 Although these last models are closer to what happens in patients with stroke, they lack reproducibility and uniformity in the resulting infarct volume, the location of the lesion, 17,18 and/or display a high degree of mortality 19 rendering the statistical analysis of the data confusing (for review, 20 ).…”
mentioning
confidence: 99%
“…Rats were anesthetized with 1.5% halothane under spontaneous respiration. Subsequent procedures for thromboembolic stroke were performed according to the methods described by Kudo et al, 12 with some added modifications. 6 The donor rat was anesthetized, and the femoral artery was catheterized with a 24-gauge elastic needle.…”
Section: Thromboembolic Stroke Modelmentioning
confidence: 99%